Study of the Morphological Characteristics of the Human Gallbladder in Relation to Age and Sex of Bangladeshi People (Bangladesh Journal of Anatomy, 2014)
Context: Variations in the morphology of the gallbladder have long been debated by the abdominal surgeons. So it is important for the surgeons to appreciate the possible anatomical variations that can be encountered during surgery to prevent post operative complications during cholecystectomy. This study was aimed at to find out any variations in the morphology of the postmortem gallbladder in adult Bangladeshi male and female to find out any difference in the gallbladder morphology in relation to age and sex. Material & methods: This study was done on sixty (60) human postmortem gallbladder from Bangladeshi male and females of two age groups- group A age between 20-40 years and group B age between 41-65 years. Among the morphological parameters length, breadth, thickness and volume of the gallbladders were measured. Result: Result of the present study showed that the mean values of gross morphological features of the gall bladder (length, breadth, thickness, volume & weight), were higher in group B than group A except the thickness in female which show somewhat higher mean value in group A than group B. The result showed significantly high value for length and volume in case of male only (p